Campus 5.0: Monitoring Vehicle Emissions for More Sustainable Mobility - Pinto, Janaina Antonino; Rodrigues, Ester Divieso Roman; Junior, Orlando Fontes Lima; Borin, Juliana Freitag; Almeida, Tania; Manera, Leandro Tiago; Makiya, Ieda Kanashiro; de Oliveira, Henrique Candido; de Sousa, Rafael Pereira; Paschoalino, Rachel de Carvalho; Braga, Vanderlei; Dalbelo, Thalita dos Santos (Journal of Sustainability Perspectives, 2024)
The university campuses are like microcities, providing employees and students with social opportunities and essential services in addition to their core educational activities (teaching, research, and outreach). The smart campus is a growing trend that makes efficient use of infrastructure by integrating smart technologies for decision-making and advancing sustainability goals. The mobility and transport project at the Unicamp University campus is part of the Smart Campus Management Technical Chamber, and the Campus 5.0 concept is aligned with several sustainable development goals outlined in the UN's 2030 Agenda. This proposal aims to develop an inventory of vehicle emissions, establish the connectivity of the information and communication network to analyze the impacts of vehicles on local air quality, and structure support models for decision-making, in addition to presenting practical solutions implemented at Unicamp aiming at greater sustainability of the campus. The information and communication network will allow the collection and analysis of data in real time, providing accurate and updated information on vehicle emissions and air quality in the campus area. Decision support models will be developed, which will allow the definition of policies and actions to promote sustainable mobility on campus, contributing to the creation of a healthier and more sustainable university environment. These results will aid university administrators in improving Green Metrics' key performance indicators.